Coordination versus capacity: quantifying the resilience contribution of airport operations centers - Madison Smith; Savannah Morgan; Joshua Trump; Benjamin Trump; Robert Horton (Environment Systems and Decisions, 2026)

Sustainable development and Africa’s critical minerals: A multi-framework approach - Macdonald Amoah; Benjamin Sovacool; Zainab Usman; Abay Yimere; Cullen S. Hendrix; Nathaniel Dolton-Thornton; Karla Cervantes Barron; Morgan Bazilian; John Ayaburi; Clarkson Kamurai (The Extractive Industries and Society, 2026)

Different effects of prenatal air pollution exposure on cord blood protein profiles and postnatal lung function in infants born to asthmatic mothers - Carla Rebeca Da Silva Sena; Olga Gorlanova; Noëmi Künstle; Gabriela Martins Costa Gomes; Andrea Marten; Sven Schulzke; Florian Wyler; Vanessa E. Murphy; Paul D. Robinson; Peter D. Sly; Jakob Usemann; Benjamin Stoecklin; et al. (Environmental Research, 2026)

Operationalizing human factors in critical infrastructure resilience stress testing: a research agenda - Elizaveta Pinigina; Ziynet Boz; Nargiza Ludgate; Gregory Kiker; Savannah Morgan; Robert Horton; Mykhailo Prazian; Volodymyr Artemchuk; Marius Laurinaitis; Benjamin D. Trump (Environment Systems and Decisions, 2026)

Quantitative assessment of knowledge gaps and research priorities for understanding and managing population irruptions of crown-of-thorns starfish (Acanthaster cf. solaris) on Australia’s Great Barrier Reef - Morgan S. Pratchett; Peter C. Doll; Christopher Cvitanovic; Shaun K. Wilson; Russell C. Babcock; Yves-Marie Bozec; Deborah Burn; Maria Byrne; Carolina Castro-Sanguino; Carla C. M. Chen; Scott A. Condie; Zara-Louise Cowan; et al. (Coral Reefs, 2026)
Despite extensive research on the western Pacific crown-of-thorns starfish (CoTS; Acanthaster cf. solaris ), especially from Australia’s Great Barrier Reef (GBR), there are persistent knowledge gaps that constrain understanding and management. Given renewed population irruptions of CoTS on the GBR, alongside escalating climate impacts and direct anthropogenic pressures, a quantitative assessment of knowledge gaps was undertaken to identify research priorities and guide future efforts. In this study, 27 experts independently scored 206 research questions across seven Themes and 39 topics, based on four different criteria ( Knowledge gap , Feasibility , Urgency , and Applicability ). These questions were ultimately rationalized into 170 distinct questions, with scores aggregated across merged questions. Management was the highest scoring Theme for Urgency , Applicability , and overall. All but six of the 20 top-ranked questions were from the Management Theme and mainly related to Culling and/ or Monitoring. Most questions (158 out of 170) also scored highly for Feasibility , suggesting that there are existing methods and technical capability available to advance the extensive and diverse range of research questions that were posed, if resources were made available. This quantitative assessment provides guidance on the prioritization of potential research that could improve management of CoTS populations to improve coral protection outcomes on the GBR. This study also suggests that there are limited constraints to undertaking necessary research to address many of the persistent knowledge gaps relating to CoTS.

Continental Drivers of Population‐Level Intraspecific Trait Variability in Salamanders, Birds, and Small Mammals - Isadora E. Fluck; Sydne Record; Angela Strecker; Phoebe L. Zarnetske; Dean C. Adams; Morgan W. Tingley; Rodney B. Siegel; Benjamin Baiser (Global Ecology and Biogeography, 2026)
Aim Intraspecific trait variability (ITV) is a key component of biodiversity because it informs how organisms respond to abiotic and biotic conditions. Understanding how the variability among individuals within a population (population‐level ITV) changes along environmental gradients offers insight into how local processes contribute to broad‐scale biodiversity patterns. Here, we examine how climate and species‐richness interact to drive population‐level ITV across taxa with distinct life‐histories. Location United States and Canada. Time Period Present. Major Taxa Studied Plethodon salamanders, birds, and small mammals. Methods Individual body‐size measurements were compiled from multiple large‐scale biodiversity data sources, and population‐level ITV across populations of the focal taxa was quantified as the coefficient of variation (CV). Using Bayesian phylogenetic generalized linear mixed models (PGLMMs), we tested the effects of mean annual temperature, precipitation, and relative humidity, as well as their interactions with species richness, while accounting for species identity, phylogeny, and site. Results The influence of environmental predictors on population‐level ITV differed across taxonomic groups. Salamander ITV declined with humidity and increased with temperature in species‐rich sites, bird ITV increased with temperature, and small‐mammal ITV decreased with precipitation but increased with humidity and temperature in species‐rich sites. Main Conclusions We found that abiotic and biotic conditions shape trait diversity within populations, and that these factors differ across taxonomic groups according to their life‐histories. Groups with relatively low mobility and that are closely tied to their microhabitats showed increased population‐level ITV in warm, species‐rich environments. These findings challenge the classic niche‐packing expectations by suggesting that responses to climatic stress and interspecific competition can increase individual variation within populations, potentially reflecting differences in the strategies individuals adopt to cope with environmental challenges. Together, these insights underscore the importance of studying intraspecific trait variation for understanding macroecological patterns in biodiversity.

How do nutrient supply and reduced tillage influence weed flora and its impact on grain maize growth under organic farming? - Christophe Lacroix; Bruno Huyghebaert; Simon Sail; Morgan Abras; Benjamin Dumont (European Journal of Agronomy, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Shortleaf Pine (Pinus echinata): Management Challenges, Knowledge Gaps, and Opportunities for an Unsung Species - Benjamin O. Knapp; Jacob Fraser; Joanne Baggs; Vikram E. Chhatre; David Clabo; Connor D. Crouch; Daniel C. Dey; Shaik M. Hossain; Steven B. Jack; John M. Kabrick; Kathryn R. Kidd; Steven McNulty; et al. (Journal of Forestry, 2026)
Shortleaf pine has the broadest range of the southern pine species, occurring in 22 states and extending north into New Jersey, Pennsylvania, and New York (Staten Island). Shortleaf pine has been understudied compared to loblolly pine and longleaf pine, typically favored for timber production and conservation value, respectively. The extensive range of shortleaf pine contributes to a high degree of variability within and among its ecosystems and contributes to the need to understand regional context in considering its ecology and management. The goal of this paper is to review and synthesize the state-of-knowledge on shortleaf pine ecosystems, emphasizing the importance of variation across its range in identifying management challenges and opportunities. We discuss the variation in growing conditions that occur across the geographic range, shortleaf pine natural community groups, and contemporary shortleaf pine forest types that occur on the landscape. We provide a review of the state-of-knowledge for topics related to shortleaf pine management, including its fire ecology, genetic considerations, economics, and others. Finally, we synthesize these into key considerations and highlight regionally specific management challenges and opportunities.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Scaling carbon capture and storage (CCS) to gigaton capacity: A multi-dimensional and critical review - Benjamin Mitterrutzner; Benjamin K. Sovacool; Brage Rugstad Knudsen; Morgan D. Bazilian; Jinsoo Kim; Simon Roussanaly; Asgeir Tomasgard; Steven Griffiths (International Journal of Greenhouse Gas Control, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Assessing behavioural economic demand for morphine after an acute dose in individuals with- and without childhood trauma: a double-blind, randomised, controlled trial - Martin Trøstheim; Benjamin L. Berey; Elizabeth R. Aston; Matthew J. Gullo; Lee Hogarth; Graham Simpson; Rupert Broomby; Celia J. Morgan; Molly Carlyle (Psychopharmacology, 2025)
Background Childhood trauma is associated with positive subjective responses to acute opioids in the laboratory. Yet, its impact on behavioural economic demand for opioids remains unclear. Because demand can predict future use and misuse, we investigated whether individuals with childhood trauma also display greater demand for opioids in the laboratory. Methods This secondary analysis used data from a double-blind, randomised, controlled, counterbalanced trial. Across two sessions, individuals with ( n = 26) and without ( n = 21) childhood trauma received a high (0.15 mg/kg) and low (0.01 mg/kg) dose of intramuscular morphine 120 min before a hypothetical purchase task. Participants also regularly reported their subjective desire for the study drug. Area under the consumption and expenditure curves, and specific demand indices ( O max , P max , breakpoint , intensity , elasticity ), were analysed with non-parametric mixed models. Results Consumption and expenditure for low dose morphine was lower in the childhood trauma group when compared to high dose morphine in this group, and low dose morphine in the control group ( p s ≤ 0.03). Consistent results were obtained for specific demand indices O max , P max , and breakpoint , but not intensity or elasticity . Positive correlations between subjective desire and consumption and expenditure were only observed in the childhood trauma group ( Tau-c = 0.24–0.34, p s ≤ 0.03). Conclusion Under laboratory conditions, desires to use opioids among individuals with childhood traumas may not manifest in strong intentions to acquire these drugs. Diverging results from psychometric measures of subjective and economic opioid value highlight the need for future research to explore contextual and resilience factors to understand how problematic opioid use emerges after childhood traumas.

Grief Among Oncology Providers: Prevalence and Association with Burnout - Shannon R. McGue; Cameron J. Oswalt; Benjamin T. Berger; Sarah S. Morgan; Sara A. Barlow; Carl F. Pieper; Linda M. Sutton; Matthew K. Labriola; Anthony N. Galanos (Journal of Cancer Education, 2025)

Holocene environmental change in Singapore: Insights from sedimentary and foraminifera records - Yu Ting Yan; Adam D. Switzer; Stephen Chua; Kyle Morgan; Christophe Fontanier; Stephen J. Culver; Abang M.S. Nugraha; Chris Gouramanis; Yama Dixit; Benjamin P. Horton (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Allometric relationships for the linear dimensions and biomass of Puerto Rican mangroves - Charles A. Price; Todd A. Schroeder; Benjamin Branoff; Skip J. Van Bloem; Nicole Pillot-Torres; Morgan H. Chaudry; Monica Papeş; Humfredo Marcano-Vega (Forest Ecology and Management, 2025)

Intracellular carbon storage of microorganisms and resulting C sequestration in biosolids-amended agricultural soil - Guanglong Tian; Olawale Oladeji; Benjamin Morgan; Essam El-Naggar; Albert Cox; Heng Zhang; Edward Podczerwinski (Soil Biology and Biochemistry, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Critical minerals mining and Native American sovereignty: Comparing case studies of lithium, copper, antimony, nickel and graphite mining in the United States - Macdonald Amoah; Benjamin K. Sovacool; Dustin Mulvaney; Morgan D. Bazilian; Richard Luarkie; Daniel Cardenas (The Extractive Industries and Society, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Spatial Nonstationarity in Phenological Responses of Nearctic Birds to Climate Variability - Benjamin A. Tonelli; Casey Youngflesh; Tyler Cox; Montague H. C. Neate‐Clegg; Emily B. Cohen; Morgan W. Tingley (Ecology Letters, 2024)
Climate change is shifting the phenology of migratory animals earlier; yet an understanding of how climate change leads to variable shifts across populations, species and communities remains hampered by limited spatial and taxonomic sampling. In this study, we used a hierarchical Bayesian model to analyse 88,965 site‐specific arrival dates from 222 bird species over 21 years to investigate the role of temperature, snowpack, precipitation, the El‐Niño/Southern Oscillation and the North Atlantic Oscillation on the spring arrival timing of Nearctic birds. Interannual variation in bird arrival on breeding grounds was most strongly explained by temperature and snowpack, and less strongly by precipitation and climate oscillations. Sensitivity of arrival timing to climatic variation exhibited spatial nonstationarity, being highly variable within and across species. A high degree of heterogeneity in phenological sensitivity suggests diverging responses to ongoing climatic changes at the population, species and community scale, with potentially negative demographic and ecological consequences.

Analysis of effects and factors linked to soil microbial populations and nitrogen cycling under long-term biosolids application - Benjamin S.T. Morgan; Guanglong Tian; Olawale O. Oladeji; Albert E. Cox; Thomas C. Granato; Heng Zhang; Edward W. Podczerwinski (Science of The Total Environment, 2024)

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Rubble persistence under ocean acidification threatened by accelerated bioerosion and lower‐density coral skeletons - Alice E. Webb; Ana M. Palacio‐Castro; Kenzie Cooke; Katherine R. Eaton; Benjamin Chomitz; Nash Soderberg; Morgan Chakraborty; Zachary Zagon; Albert Boyd; Patrick M. Kiel; Allyson DeMerlis; Chris T. Perry; et al. (Global Change Biology, 2024)
As the balance between erosional and constructive processes on coral reefs tilts in favor of framework loss under human‐induced local and global change, many reef habitats worldwide degrade and flatten. The resultant generation of coral rubble and the beds they form can have lasting effects on reef communities and structural complexity, threatening the continuity of reef ecological functions and the services they provide. To comprehensively capture changing framework processes and predict their evolution in the context of climate change, heavily colonized rubble fragments were exposed to ocean acidification (OA) conditions for 55 days. Controlled diurnal pH oscillations were incorporated in the treatments to account for the known impact of diel carbonate chemistry fluctuations on calcification and dissolution response to OA. Scenarios included contemporary pH (8.05 ± 0.025 diel fluctuation), elevated OA (7.90 ± 0.025), and high OA (7.70 ± 0.025). We used a multifaceted approach, combining chemical flux analyses, mass alteration measurements, and computed tomography scanning images to measure total and chemical bioerosion, as well as chemically driven secondary calcification. Rates of net carbonate loss measured in the contemporary conditions (1.36 kg m −2 year −1 ) were high compared to literature and increased in OA scenarios (elevated: 1.84 kg m −2 year −1 and high: 1.59 kg m −2 year −1 ). The acceleration of these rates was driven by enhanced chemical dissolution and reduced secondary calcification. Further analysis revealed that the extent of these changes was contingent on the density of the coral skeleton, in which the micro‐ and macroborer communities reside. Findings indicated that increased mechanical bioerosion rates occurred in rubble with lower skeletal density, which is of note considering that corals form lower‐density skeletons under OA. These direct and indirect effects of OA on chemical and mechanical framework‐altering processes will influence the permanence of this crucial habitat, carrying implications for biodiversity and reef ecosystem function.

Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

AgAnimalGenomes: browsers for viewing and manually annotating farm animal genomes - Deborah A. Triant; Amy T. Walsh; Gabrielle A. Hartley; Bruna Petry; Morgan R. Stegemiller; Benjamin M. Nelson; Makenna M. McKendrick; Emily P. Fuller; Noelle E. Cockett; James E. Koltes; Stephanie D. McKay; Jonathan A. Green; et al. (Mammalian Genome, 2023)
Current genome sequencing technologies have made it possible to generate highly contiguous genome assemblies for non-model animal species. Despite advances in genome assembly methods, there is still room for improvement in the delineation of specific gene features in the genomes. Here we present genome visualization and annotation tools to support seven livestock species (bovine, chicken, goat, horse, pig, sheep, and water buffalo), available in a new resource called AgAnimalGenomes. In addition to supporting the manual refinement of gene models, these browsers provide visualization tracks for hundreds of RNAseq experiments, as well as data generated by the Functional Annotation of Animal Genomes (FAANG) Consortium. For species with predicted gene sets from both Ensembl and RefSeq, the browsers provide special tracks showing the thousands of protein-coding genes that disagree across the two gene sources, serving as a valuable resource to alert researchers to gene model issues that may affect data interpretation. We describe the data and search methods available in the new genome browsers and how to use the provided tools to edit and create new gene models.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Perspectives on strengthening local food systems in Small Island Developing States - Cornelia Guell; Catherine R. Brown; Otto W. Navunicagi; Viliamu Iese; Neela Badrie; Morgan Wairiu; Arlette Saint Ville; Nigel Unwin; Sashi Kiran; T. Alafia Samuels; Ian Hambleton; Colin Tukuitonga; et al. (Food Security, 2022)
Small Island Developing States (SIDS) share high burdens of nutrition-related conditions, including non-communicable diseases, associated with an increasing reliance on imported, processed foods. Improving health through increasing the production and consumption of local, nutritious foods is a policy objective of many SIDS governments. This study aimed to understand contemporary challenges and opportunities to strengthening local food systems in two case study settings, Fiji and St. Vincent and the Grenadines. Fifty-two in-depth, semi-structured interviews were conducted with key stakeholders involved in local food production. Interviews were analysed by both country teams using thematic analysis. Local food production networks in both settings included formal governance bodies as well as more informal connections through civil society and communities. Their main function was the sharing of resources and knowledge, but levels of trust and cooperation between the stakeholders varied in a market open to intense competition from imports. Local food production was hindered by few and slow investments by local governments, dated technology, and lack of knowledge. Stakeholders believed this marginalisation was occurring against a background of rising preferences for imported foods in the population, and increasing disinterest in employment in the sector. Despite the challenges, strong narratives of resilience and opportunity were highlighted such as national pride in local produce for commercialisation and local diets. Efforts to support local food production in SIDS should focus on strengthening governance structures to prioritise local produce over corporate and import markets, assist collaboration and co-learning, and support alternative agro-food practices.

Increasing threat of wildfires: the year 2020 in perspective: A Global Ecology and Biogeography special issue - Rachael H. Nolan; Liana O. Anderson; Benjamin Poulter; J. Morgan Varner (Global Ecology and Biogeography, 2022)
Aim Each year, wild and managed fires burn roughly 4 million km 2 [~400 million hectares (Mha)] of savanna, forest, grassland and agricultural ecosystems. Land use and climate change have altered fire regimes throughout the world, with a trend toward higher‐severity fires found from Australia, the Americas, Europe and Asia, to the Arctic. In 2020, there were notable catastrophic fires in Australia (in the 2019/20 Austral fire season), the Western United States, South America and Siberia. These fires defined much of the global fire year and were compounded by the socio‐economic disruption of the Coronavirus 2019 (COVID‐19) pandemic. Location Global. Time period 2020. Major taxa studied Flora and fauna. Methods The Global Ecology and Biogeography special issue, ‘Increasing threat of wildfires: the year 2020 in perspective’, includes 18 papers that catalogue these fire events, their drivers and their impacts on flora and fauna. Results Collectively, these papers highlight the importance of fire response traits, exposure and sensitivity to interacting threats in determining fire impacts. Main conclusions The scale of the 2020 megafires has helped identify new research areas required to more comprehensively assess fire impacts on biodiversity and biogeochemistry and to inform ecosystem management.

Characterisation of carapace composition in developing and adult ostracods (Skogsbergia lerneri) and its potential for biomaterials - Benjamin M. Rumney; Siân R. Morgan; J. Frederick W. Mosselmans; F. Tegwen Malik; Simon J. Holden; Andrew R. Parker; Nick White; Philip N. Lewis; Julie Albon; Keith M. Meek (Marine Biology, 2022)
The protective carapace of Skogsbergia lerneri, a marine ostracod, is scratch-resistant and transparent. The compositional and structural organisation of the carapace that underlies these properties is unknown. In this study, we aimed to quantify and determine the distribution of chemical elements and chitin within the carapace of adult ostracods, as well as at different stages of ostracod development, to gain insight into its composition. Elemental analyses included X-ray absorption near-edge structure, X-ray fluorescence and X-ray diffraction. Nonlinear microscopy and spectral imaging were performed to determine chitin distribution within the carapace. High levels of calcium (20.3%) and substantial levels of magnesium (1.89%) were identified throughout development. Amorphous calcium carbonate (ACC) was detected in carapaces of all developmental stages, with the polymorph, aragonite, identified in A-1 and adult carapaces. Novel chitin-derived second harmonic generation signals (430/5 nm) were detected. Quantification of relative chitin content within the developing and adult carapaces identified negligible differences in chitin content between developmental stages and adult carapaces, except for the lower chitin contribution in A-2 (66.8 ± 7.6%) compared to A-5 (85.5 ± 10%) ( p = 0.03). Skogsbergia lerneri carapace calcium carbonate composition was distinct to other myodocopid ostracods. These calcium polymorphs and ACC are described in other biological transparent materials, and with the consistent chitin distribution throughout S. lerneri development, may imply a biological adaptation to preserve carapace physical properties. Realisation of S. lerneri carapace synthesis and structural organisation will enable exploitation to manufacture biomaterials and biomimetics with huge potential in industrial and military applications.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The ultrastructural development and 3D reconstruction of the transparent carapace of the ostracod Skogsbergia lerneri - Benjamin M. Rumney; F. Tegwen Malik; Siân R. Morgan; Andrew R. Parker; Simon Holden; Julie Albon; Philip N. Lewis; Keith M. Meek (Marine Biology, 2022)
The Skogsbergia lerneri is a marine ostracod which possesses a carapace that is both protective and transparent. Since development of this carapace and how it is maintained in the adult is not known, the aim of this investigation was to carry out an in-depth ultrastructural study of the ostracod carapace at different developmental stages. Standard transmission electron microscopy and novel serial block face scanning electron microscopy (SBF-SEM) were undertaken to discern carapace ultrastructure in both two and three dimensions. Analysis revealed a carapace consisting of the same basic layer structure as other myodocopid ostracods, namely an epicuticle, exocuticle, endocuticle and membranous layer, but with a thinner adult carapace of mean thickness of 19.2 ± 1.78 µm, n = 5. The carapace layers, except for instar 1 ostracods, had similar relative proportions throughout development. The endocuticle and membranous layer thickened through advancing developmental stages due to an increase in calcified crystalline polyhedrons and a greater number of chitinous lamellae in the membranous layer. Crystalline polyhedron dimensions were significantly smaller near the boundary with the membranous layer. The borders between the carapace layers were indistinct; SBF-SEM revealed an abundance of epicuticle projections into the exocuticle and apparent gradual merging at the boundary of the exocuticle and the endocuticle. Here, we discuss how the S. lerneri carapace layer structure has evolved to serve a specific mechanical function, allowing surface protection and rigidity. In addition, we suggest that the lack of pigment and graduated layer boundaries contribute to the transparency of the carapace.

The ID NOW COVID-19, a high-speed high-performance assay - Eric Farfour; M. Asso-Bonnet; M. Vasse; Emilie Catherinot; Colas Tcherakian; Antoine Magnan; Simon Chauveau; Sylvie Colin de Verdière; Hélène Salvatore; Antoine Roux; Benjamin Zuber; Charles Cerf; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Resting fMRI-guided TMS results in subcortical and brain network modulation indexed by interleaved TMS/fMRI - Desmond J. Oathes; Jared P. Zimmerman; Romain Duprat; Seda S. Japp; Morgan Scully; Benjamin M. Rosenberg; Matthew W. Flounders; Hannah Long; Joseph A. Deluisi; Mark Elliott; Gavriella Shandler; Russell T. Shinohara; et al. (Experimental Brain Research, 2021)

Establishment of long-term ostracod epidermal culture - Siân R. Morgan; Laura Paletto; Benjamin Rumney; Farhana T. Malik; Nick White; Philip N. Lewis; Andrew R. Parker; Simon Holden; Keith M. Meek; Julie Albon (In Vitro Cellular & Developmental Biology - Animal, 2020)
Primary crustacean cell culture was introduced in the 1960s, but to date limited cell lines have been established. Skogsbergia lerneri is a myodocopid ostracod, which has a body enclosed within a thin, durable, transparent bivalved carapace, through which the eye can see. The epidermal layer lines the inner surface of the carapace and is responsible for carapace synthesis. The purpose of the present study was to develop an in vitro epidermal tissue and cell culture method for S. lerneri . First, an optimal environment for the viability of this epidermal tissue was ascertained, while maintaining its cell proliferative capacity. Next, a microdissection technique to remove the epidermal layer for explant culture was established and finally, a cell dissociation method for epidermal cell culture was determined. Maintenance of sterility, cell viability and proliferation were key throughout these processes. This novel approach for viable S. lerneri epidermal tissue and cell culture augments our understanding of crustacean cell biology and the complex biosynthesis of the ostracod carapace. In addition, these techniques have great potential in the fields of biomaterial manufacture, the military and fisheries, for example, in vitro toxicity testing.

Channeling Effect and Tissue Morphology in a Perfusion Bioreactor Imaged by X-Ray Microtomography - Claire C. Beauchesne; Morgan Chabanon; Benjamin Smaniotto; Benoît Ladoux; Benoît Goyeau; Bertrand David (Tissue Engineering and Regenerative Medicine, 2020)

Characterization of Autism Spectrum Disorder across the Age Span by Intrinsic Network Patterns - Benjamin R. Morgan; George M. Ibrahim; Vanessa M. Vogan; Rachel C. Leung; Wayne Lee; Margot J. Taylor (Brain Topography, 2019)

Recent ecological change in ancient lakes - Stephanie E. Hampton; Suzanne McGowan; Ted Ozersky; Salvatore G. P. Virdis; Tuong Thuy Vu; Trisha L. Spanbauer; Benjamin M. Kraemer; George Swann; Anson W. Mackay; Stephen M. Powers; Michael F. Meyer; Stephanie G. Labou; et al. (Limnology and Oceanography, 2018)
Ancient lakes are among the best archivists of past environmental change, having experienced more than one full glacial cycle, a wide range of climatic conditions, tectonic events, and long association with human settlements. These lakes not only record long histories of environmental variation and human activity in their sediments, but also harbor very high levels of biodiversity and endemism. Yet, ancient lakes are faced with a familiar suite of anthropogenic threats, which may degrade the unusual properties that make them especially valuable to science and society. In all ancient lakes for which data exist, significant warming of surface waters has occurred, with a broad range of consequences. Eutrophication threatens both native species assemblages and regional economies reliant on clean surface water, fisheries, and tourism. Where sewage contributes nutrients and heavy metals, one can anticipate the occurrence of less understood emerging contaminants, such as pharmaceuticals, personal care products, and microplastics that negatively affect lake biota and water quality. Human populations continue to increase in most of the ancient lakes’ watersheds, which will exacerbate these concerns. Further, human alterations of hydrology, including those produced through climate change, have altered lake levels. Co‐occurring with these impacts have been intentional and unintentional species introductions, altering biodiversity. Given that the distinctive character of each ancient lake is strongly linked to age, there may be few options to remediate losses of species or other ecosystem damage associated with modern ecological change, heightening the imperative for understanding these systems.

Altered white matter development in children born very preterm - Julia M. Young; Marlee M. Vandewouw; Benjamin R. Morgan; Mary Lou Smith; John G. Sled; Margot J. Taylor (Brain Structure and Function, 2018)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Moving Towards a New Urban Systems Science - Peter M. Groffman; Mary L. Cadenasso; Jeannine Cavender-Bares; Daniel L. Childers; Nancy B. Grimm; J. Morgan Grove; Sarah E. Hobbie; Lucy R. Hutyra; G. Darrel Jenerette; Timon McPhearson; Diane E. Pataki; Steward T. A. Pickett; et al. (Ecosystems, 2017)

Apolipoprotein E ε4 genotype status is not associated with neuroimaging outcomes in a large cohort of HIV+ individuals - Sarah A. Cooley; Robert H. Paul; Christine Fennema-Notestine; Erin E. Morgan; Florin Vaida; Qianqian Deng; Jie Ashley Chen; Scott Letendre; Ronald Ellis; David B. Clifford; Christina M. Marra; Ann C. Collier; et al. (Journal of NeuroVirology, 2016)

An amniote life‐history database to perform comparative analyses with birds, mammals, and reptiles - Nathan P. Myhrvold; Elita Baldridge; Benjamin Chan; Dhileep Sivam; Daniel L. Freeman; S. K. Morgan Ernest (Ecology, 2015)
Studying life‐history traits within and across taxonomic classifications has revealed many interesting and important patterns, but this approach to life history requires access to large compilations of data containing many different life‐history parameters. Currently, life‐history data for amniotes (birds, mammals, and reptiles) are split among a variety of publicly available databases, data tables embedded in individual papers and books, and species‐specific studies by experts. Using data from this wide range of sources is a challenge for conducting macroecological studies because of a lack of standardization in taxonomic classifications, parameter values, and even in which parameters are reported. In order to facilitate comparative analyses between amniote life‐history data, we created a database compiled from peer‐reviewed studies on individual species, macroecological studies of multiple species, existing life‐history databases, and other aggregated sources as well as published books and other compilations. First, we extracted and aggregated the raw data from the aforementioned sources. Next, we resolved spelling errors and other formatting inconsistencies in species names through a number of computational and manual methods. Once this was completed, subspecies‐level data and species‐level data were shared via a data‐sharing algorithm to accommodate the variety of species transformations (taxonomic promotions, demotions, merges, divergences, etc.) that have occurred over time. Finally, in species where multiple raw data points were identified for a given parameter, we report the median value. Here, we report a normalized and consolidated database of up to 29 life‐history parameters, containing at least one life‐history parameter for 21 322 species of birds, mammals, and reptiles.

Selection on non‐social traits limits the invasion of social cheats - Andrew D. Morgan; Benjamin J. Z. Quigley; Sam P. Brown; Angus Buckling (Ecology Letters, 2012)
While the conditions that favour the maintenance of cooperation have been extensively investigated, the significance of non‐social selection pressures on social behaviours has received little attention. In the absence of non‐social selection pressures, patches of cooperators are vulnerable to invasion by cheats. However, we show both theoretically, and experimentally with the bacterium Pseudomonas fluorescens , that cheats may be unable to invade patches of cooperators under strong non‐social selection (both a novel abiotic environment and to a lesser extent, the presence of a virulent parasite). This is because beneficial mutations are most likely to arise in the numerically dominant cooperator population. Given the ubiquity of novel selection pressures on microbes, these results may help to explain why cooperation is the norm in natural populations of microbes.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.